2012
DOI: 10.1017/s0007114512000670
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of digestive function is retarded and plasma antioxidant capacity lowered in fully weaned low birth weight piglets

Abstract: The digestive function of low birth weight (LBW) pigs post-weaning has been poorly studied. Therefore, newborns from eleven hyperprolific sows were weighed, weaned at 27·2 d and fed a starter diet until sampling. Sampling was done between 18 and 28 d post-weaning. An LBW piglet (n 19) was defined as a piglet having a birth weight less than 1 kg and less than the lower quartile of litter birth weights. Normal birth weight (NBW) piglets (n 13) were having a birth weight close to the mean litter birth weight. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
62
3
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 45 publications
(67 reference statements)
10
62
3
5
Order By: Relevance
“…Our findings agree with previous observations that also suggested that IUGR was associated with poorly developed SIs, which were shorter and thinner than those of normal piglets, although the relative length of the SI in IUGR was longer (Wang et al 2005;D'Inca et al 2010c;Shanklin and Cooke 1993). Michiels et al (2013) also reported maldevelopment of the digestive tract of the IUGR piglets in the post-weaning period. This could be a consequence of lower circulating insulin-like growth factor-1 (IGF-1) levels.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings agree with previous observations that also suggested that IUGR was associated with poorly developed SIs, which were shorter and thinner than those of normal piglets, although the relative length of the SI in IUGR was longer (Wang et al 2005;D'Inca et al 2010c;Shanklin and Cooke 1993). Michiels et al (2013) also reported maldevelopment of the digestive tract of the IUGR piglets in the post-weaning period. This could be a consequence of lower circulating insulin-like growth factor-1 (IGF-1) levels.…”
Section: Discussionsupporting
confidence: 92%
“…Using the same assay, the majority of IGF-1 levels were also below detection limit in preterm infants during the first month of life (24). The slightly reduced relative liver weight, and increased kidney weight at 26 days, may relate to this metabolic dysregulation, together with changes in other endocrine control mechanisms, e.g., reduced sensitivity to insulin or IGF-1, as shown for growth-restricted piglets (38).…”
Section: Discussionmentioning
confidence: 77%
“…This was termed the ‘catch-up fat phenomenon,’ whereas the rebuilding of muscles was delayed [32]. It has been reported previously that the development of the gastrointestinal tract of IUGR pigs and the maturation of the digestive function post-weaning were delayed [13, 33, 34]. This is thought to contribute to a reduced efficiency of nutrient utilization during growth [8].…”
Section: Discussionmentioning
confidence: 99%